Pathogenic Bacterial Genes Resistant to Antibiotics in Chickens: Systematic Literature Review - Rosyunita Rosyunita; Eustachius Hagni Wardoyo; Nurmi Hasbi; Adelia Riezka Rahim (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
Chicken meat and eggs are widely consumed sources of protein, increasing consumer demand and leading to the use of antibiotics as prophylaxis and therapeutics. The purpose of this narrative review is to describe the colonization of chicken parts and organs and summarize the resistance genes in chickens reported from 2015 to 2026. The method used a systematic literature review with a narrative review. This review focuses on four main bacteria: Escherichia coli, Salmonella spp., Campylobacter spp., and Enterococcus spp. The results showed that almost all chicken organs were colonized by bacteria carrying various antibiotic resistance genes. These resistance genes included fluoroquinolones (gyrA, gyrB), tetracyclines (tetA, tetB, tetO, tetM, tetL), β-lactams (blaTEM, blaSHV, blaCTX-M, blaCMY, blaOXA-61), aminoglycosides (aac, aad, aph, strA/B), and sulfonamides (sul1, sul2, sul3). The presence of multidrug efflux pump genes (cmeB, cmeG) in Campylobacter spp. further highlights the increasing prevalence of multidrug resistance. Colonization of antibiotic-resistant pathogenic bacteria with resistance genes has been found in vital organs of chickens. These findings highlight the importance of molecular surveillance and integrated One Health strategies to reduce the spread of AMR.